2020
DOI: 10.3390/en14010129
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Models of Accidents at Work in the Steel Sector as a Framework for Sustainable Safety

Abstract: Work safety can be a component of the broadly understood sustainable enterprise approach that goes beyond the idea of sustainable development. Sustainability in an unpredictable and turbulent environment has many constellations, many aspects and many fields of the enterprise’s activity and it complements the rationality of the business. The aim is to understand the sustainability of safety, because this is the term we have adopted for rationality in occupational safety management, in the context of the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Among the first publications were those presenting the use of autonomous technologies for product quality control during ongoing metallurgical processes [77,78,79,80]. The full automation of metallurgical processes was becoming a necessity, if only because of the high risk for employees, who had to work at very high temperatures and come into contact with other risks to their health and life [81,82]. Along with automation, IT technologies were entering the steel mills.…”
Section: Discussionmentioning
confidence: 99%
“…Among the first publications were those presenting the use of autonomous technologies for product quality control during ongoing metallurgical processes [77,78,79,80]. The full automation of metallurgical processes was becoming a necessity, if only because of the high risk for employees, who had to work at very high temperatures and come into contact with other risks to their health and life [81,82]. Along with automation, IT technologies were entering the steel mills.…”
Section: Discussionmentioning
confidence: 99%
“…In the second step, the accuracy of forecasts was assessed by means of ex post forecast errors used in the relevant literature on forecasting [21][22][23][24]26,[43][44][45][46][47][48][49]]:…”
Section: Purpose and Methodology Of Researchmentioning
confidence: 99%
“…empirical data; y t *, forecasts value; n, number of elements of the time series; m, number of initial time moments t. For the listed errors, the following limiting assumptions were made[21,23,42,49]: • adjusted average relative ex post error Θ-the error value should be in the range from <0-200%>; • mean error ψ, the error value should not exceed 10%; • mean absolute error MAE, the error value should satisfy the relationship that occurs between the measures-MAE ≤ RMSE; • root mean square error (RMSE) takes values less than or equal to the standard deviation of the S e model residuals. The standard deviation of the model residuals is determined from the relationship (5):…”
mentioning
confidence: 99%
“…Very high temperature, noise or dust. Analyzing the period from 2009 to 2018, the authors found that the number of people injured in accidents in the steel sector was 967 injured per year [47]. Apart from the causes not controlled by humans (explosion, fire, ignition of materials), there are technical reasons (defect of the material factor and poor state of security) and human (disregarding the hazard, insufficient concentration of attention, improper use of limbs in the danger zone, surprise by an unexpected event, improper working methods, non-compliance with health and safety regulations, failure to use safety footwear by the employee, performing activities without removing the risk, other (e.g.…”
Section: Key Directions For Industry 40 In the Steel Sec-tor Transfor...mentioning
confidence: 99%